Understanding market preference for fresh fruits and vegetables: A choice experiment approach - Chege, Christine Gacheri Kiria; Wanyama, R.; Onyango, Kevin; Kabach, J.; Lundy, Mark M. (2021)
Evidence shows that consumption of fresh fruits and vegetables (FFV) in most low-and middle-income countries remains significantly below the recommended dietary requirements (Willet et al., 2019). This is attributed to multiple interrelated factors including limited availability, accessibility, affordability, and culture and preferences. Especially in low-income urban households, high price of FFV is a significant constraint towards their adequate consumption (Schreinemachers et al., 2018). Even so, price is often seen as a function of a combination of product attributes and individual characteristics, which influence buyers’ decisions, and not the product itself. While it is important to understand the drivers of FFV intake among consumers, focusing on one end of the value chain may not reveal the complexity of factors influencing consumption. Understanding the behavior of other value chain actors may contribute to enhancing the efficiency of the value chain to make FFV more available, and thus accessible to low-income consumers. A lot of studies focus on commodity attributes preferred by consumers (references). Recent studies show that the food environment , the space where consumers interact with food, has an influence on consumer behavior and diets. The kind of food made available, accessible and affordable to consumers and how they are presented to the, influence what consumers eat which eventually has and influence on their diets, nutrition and health (Chege et al., 2021; Herforth, and Ahmed, (2015). This study seeks to understand market preferences for FFV by focusing on vendors operating in poor urban neighborhoods of Nairobi, Kenya. This is important for several reasons; first, vendors preferences are a reflection of consumer preferences, so this will also help to understand attributes consumers look for when buying FFV. Secondly, the results from this study would provide important information on how FFV wholesalers can package their product to meet vendors’ preferences.